Christian Education Correlation With The Moral of Student's Developments - Windarti, Maria Titik; Mariana, Evi; Rina, Rina; Sarmauli, Sarmauli (Jurnal Pendidikan Agama Kristen (JUPAK), 2024)
The moral formation of a child is first found in the family, so education at school adds more formation and knowledge to strengthen his personality. Because in school a child learns in three domains, namely cognitive, affective, and psychomotor, cooperation, responsibility, respect, and even to recognize himself. The reality is that students learn do not have advantages and uniqueness personally but on the contrary student achievement decreases, does not carry out their obligations as students to learn, and does not know themselves. There is a very significant positive relationship between Christian religious education and the moral formation of students at Pelita Bangsa Christian Middle School Bandung in the 2019/2020 school year, this is indicated by the product-moment correlation value of 0.737 with a significant level of 0.05.